2012
DOI: 10.1007/s12528-012-9059-x
|View full text |Cite
|
Sign up to set email alerts
|

Online learning in management education: an empirical study of the role of personality traits

Abstract: In this study we seek to better understand the outcomes of online education by observing the role of learners' personality traits. Under the premise that the behaviors that maximize learning are contingent on the delivery method, we compared learning outcomes of students participating in four sections of an undergraduate principles of management course-three sections were taught using the online approach and one section was taught using the classroom teaching approach (N = 132). Following a multi-group quasi-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Cochran et al (2013) also found students with high previous academic achievement are more likely to persist in online courses. Varela, Cater, and Michel (2012) noted achievement orientation is a significant predictor of online learning success. Furthermore, McDaniel, DiPrete, Buchmann, and Shwed (2011) discovered educational attainment among African American males is more likely when there is no delay between high school graduation and college enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…Cochran et al (2013) also found students with high previous academic achievement are more likely to persist in online courses. Varela, Cater, and Michel (2012) noted achievement orientation is a significant predictor of online learning success. Furthermore, McDaniel, DiPrete, Buchmann, and Shwed (2011) discovered educational attainment among African American males is more likely when there is no delay between high school graduation and college enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, conscientiousness was related to the mean performance over three exams, but mostly due to achievement drive (a subset of the conscientiousness items). As the predictive values of the personality measures on performance were stronger for online than in-class students (Varela et al, 2012), this suggests that a better understanding of who is likely to be successful in online learning settings is needed to develop material to increase the likelihood of success for all students in online learning settings.…”
Section: Who Is Using Online Learning Successfully?mentioning
confidence: 99%
“…Flexibility is characterized by the ability of the student to have relative control over when to study, attend classes, and, in many cases, take their exams in online courses. This flexibility has been found to appeal to non-traditional students (Li & Irby, 2008;Shih et al, 2003;Varela, Cater, & Michel, 2012).…”
Section: Non-traditional Student Preferencesmentioning
confidence: 99%